Plasmodium falciparum merozoite surface protein 1 as asexual blood stage malaria vaccine candidate - Richard Thomson-Luque; Thomas C Stabler; Kristin Fürle; Joana C Silva; Claudia Daubenberger (Taylor & Francis Group, 2024)
ABSTRACTIntroduction Malaria represents a public health challenge in tropical and subtropical regions, and currently deployed control strategies are likely insufficient to drive elimination of malaria. Development and improvement of malaria vaccines might be key to reduce disease burden. Vaccines targeting asexual blood stages of the parasite have shown limited efficacy when studied in human trials conducted over the past decades.Areas covered Vaccine candidates based on the merozoite surface protein 1 (MSP1) were initially envisioned as one of the most promising approaches to provide immune protection against asexual blood-stage malaria. Successful immunization studies in monkey involved the use of the full-length MSP1 (MSP1FL) as vaccine construct. Vaccines using MSP1FL for immunization have the potential benefit of including numerous conserved B-cell and T-cell epitopes. This could result in improved parasite strain-transcending, protective immunity in the field. We review outcomes of clinical trials that utilized a variety of MSP1 constructs and formulations, including MSP1FL, either alone or in combination with other antigens, in both animal models and humans.Expert opinion Novel approaches to analyze breadth and magnitude of effector functions of MSP1-targeting antibodies in volunteers undergoing experimental vaccination and controlled human malaria infection will help to define correlates of protective immunity.